1997
DOI: 10.1590/s0066-782x1997001100006
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento da pressão arterial em filhos de normotensos e filhos de hipertensos submetidos a estímulos pressóricos

Abstract: Purpose Comportamento da Pressão Arterial em Filhos de Normotensos e Filhos de Hipertensos Submetidos a Estímulos Pressóricos Artigo OriginalA hipertensão arterial (HA) é uma enfermidade que acomete cerca de 15% da população adulta brasileira 1 , com tendência a elevar sua prevalência com o aumento da faixa etária 2 . Representa um importante problema sob o ponto de vista de saúde pública, uma vez que compromete o sistema cardiovascular e a função renal, levando o indivíduo ao afastamento temporário ou definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
1
Order By: Relevance
“…Differences in reported blood pressure responses could be partly or collectively explained by (i) basal blood pressure differences, (ii) variations in body fat distribution [91], (iii) differences in participants' age, since cardiovagal autonomic function undergoes a gradual maturation during childhood [92], and (iv) method of blood pressure measurement (continuous beat-by-beat finger photoplethysmography, or intermittently every 60 or 120 s by a conventional aneroid sphygmomanometer). Genetic factors and family history of hypertension can also be contributing factors, since offsprings of parents with a family history of hypertension exhibit higher basal blood pressure levels and greater mean arterial pressure during mental stress and handgrip exercise than children of normotensive parents [93]. Low fitness levels can also exaggerate the blood pressure response to exercise in children with obesity.…”
Section: Control Of Blood Pressure At Rest and During Exercise In mentioning
confidence: 99%
“…Differences in reported blood pressure responses could be partly or collectively explained by (i) basal blood pressure differences, (ii) variations in body fat distribution [91], (iii) differences in participants' age, since cardiovagal autonomic function undergoes a gradual maturation during childhood [92], and (iv) method of blood pressure measurement (continuous beat-by-beat finger photoplethysmography, or intermittently every 60 or 120 s by a conventional aneroid sphygmomanometer). Genetic factors and family history of hypertension can also be contributing factors, since offsprings of parents with a family history of hypertension exhibit higher basal blood pressure levels and greater mean arterial pressure during mental stress and handgrip exercise than children of normotensive parents [93]. Low fitness levels can also exaggerate the blood pressure response to exercise in children with obesity.…”
Section: Control Of Blood Pressure At Rest and During Exercise In mentioning
confidence: 99%
“…But this correlation index is increased between parents and consanguineous children, even though they have the same habits, Absence of significant differences for food intake between offspring of hypertensive individuals and offspring of normotensive individuals. suggesting a strong genetic influence in the pattern of blood pressure [22][23][24][25] . In our study, lower values of HDL-C were observed between the offspring of hypertensive patients, despite the similar body mass index and dietary habits in the intake of monounsaturated, polyunsaturated, and saturated fat, as well as carbohydrates and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Sua incidência entre adolescentes é de 6 a 8% (1) . Os fatores de risco para sua instalação são divididos em: modificáveis, relacionados a hábitos de vida, como sedentarismo (2) , ingestão de sal e gordura (1) , excesso de peso (2)(3)(4) , aspectos emocionais como irritação e depressão (5) , uso de drogas ilí-citas (1) ; não modificáveis, relacionados a características herdadas ou inalteráveis, como herança familiar (3,(6)(7)(8) , raça, sexo, idade (1) , baixo peso ao nascer (9)(10)(11) . Todos estes fatores são encontrados nas populações mais jovens.…”
Section: Introductionunclassified